Serum Myeloperoxidase Activity, Total Antioxidant Capacity and Nitric Oxide Levels in Patients with Chronic Otitis Media - Garça, Mehmet Fatih (Springer New York, 2013)
It has been suggested that oxidative stress may play an important role in the pathogenesis of chronic otitis media (COM), but the role of oxidative stress in the pathogenesis of COM has not yet been fully explored. Therefore, the aim of this study was to investigate serum myeloperoxidase (MPO) activity, 4-hydroxynonenal (4-HNE), malondialdehyde (MDA), total antioxidant capacity (TAC) and nitric oxide (NO) in patients with COM. Sixty-one patients with COM and 30 controls were enrolled in the present study. Patients were divided into two groups according to the presence (n = 21) or absence (n = 40) of cholesteatoma. Serum MPO activity and 4-HNE, MDA and NO levels were significantly higher in patients with COM than controls (for all, p < 0.001), while TAC levels were significantly lower (for all, p < 0.001). Serum MPO activity and MDA, 4-HNE and NO levels were significantly higher in patients with cholesteatoma than in those without cholesteatoma, while TAC levels were significantly lower; but the difference between groups was not statistically significant (p > 0.05). Increased oxidative stress seems to be associated with decreased antioxidant levels in patients with COM. Thus, increased oxidative stress may play a role in the pathogenesis of COM. It is believed that the administration of antioxidant vitamins such as A, C and E may be useful in preventing and treating COM.